Challenges in Spreading Knowledge of Da’wah Cyber - Safi'i, Imam (Anjasmoro: Islamic Interdisciplinary Journal, 2023)
The science of cyber preaching is a science that invites towards goodness and avoids evil by using various distribution mediums, especially the cyber world through the internet regardless of time and distance limits. The spread of da'wah knowledge has started since the time of the Prophet s.a.w., Companions, Tabi'in, Tabi' at-tabi'in and up to the present technology era by using various dissemination mediums. The purpose of this study is to identify the knowledge of cyber da'wah, a comparison of the methods of spreading traditional and cyber da'wah knowledge, identify the value and ethics of spreading cyber da'wah knowledge as well as the constraints in the dissemination of cyber da'wah knowledge. This study was conducted using the library method or literature review from various scientific sources as a reference for the study. At the end of the writing of this article, the challenge in spreading the knowledge of cyber da'wah can be concluded as a medium that must be taken as an opportunity by preachers today as well as the public who want to spread widely about Islamic da'wah by taking into account values and ethics when spreading through cyber is used. Challenges in spreading the knowledge of cyber preaching are always there, but as a preacher you should be wise in facing the current technology era without having a negative impact on Islam or other religions.